Perencanaan Counterweight untuk Meningkatkan Kestabilan Lereng dan Kapasitas Disposal pada Area Disposal T4 PT Unggul Dinamika Utama Provinsi Kalimantan Timur - Nurfitri Kasran; Revia Oktaviani; Ardhan Ismail; Tommy Trides; Albert Juvensius Pontus (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
The stability of disposal slopes is a critical aspect of open-pit mining operations because it directly affects operational safety and the continuity of overburden dumping activities. Disposal areas composed of overburden materials generally exhibit heterogeneous characteristics, particularly when soft materials such as mud are present, which can significantly reduce slope stability. Therefore, a comprehensive slope stability evaluation is required prior to further disposal development. This study aims to assess the stability condition of a disposal slope under initial conditions, evaluate the influence of material conditions, and analyze the effectiveness of counterweight application in improving both the safety factor and disposal capacity. The research methodology involved the collection of primary and secondary data, including slope geometry, lithological conditions, and the physical and mechanical properties of disposal materials obtained from laboratory testing and company technical data. Slope stability analysis was performed using the limit equilibrium method with the assistance of geotechnical software, taking into account groundwater conditions and operational loading. The analysis results indicate that the initial disposal condition yielded a safety factor of 0.718, indicating an unstable slope condition. After simulating the removal of mud material, the safety factor increased to 0.907 but remained below acceptable stability criteria. The application of a counterweight significantly improved slope stability, resulting in a safety factor of 1.498. Further optimization through slope geometry redesign produced a final safety factor of 1.101, which satisfies the requirements stipulated in KEPMEN ESDM No. 1827 K/30/MEM/2018. Additionally, the redesign increased the disposal capacity from 119,507,864.23 LCM to 119,682,378.22 LCM, representing an increase of 174,513.99 LCM. These results demonstrate that counterweight application combined with geometric optimization is effective in enhancing both slope stability and disposal capacity.